The Representation of Islam in European Parliament Sessions: A Corpus Study of ‘Europarl 3: German’ - Lestari, Tri Edliani; Anwar, Miftahulkhairah; Prihantoro, Prihantoro (Jurnal Ilmiah Global Education, 2024)
This study investigates the representation of Islam in European Parliament sessions using the Europarl 3: German corpus, focusing on collocations related to Islam to understand their associated sentiments and semantic distributions. Political discourse plays a critical role in shaping public perceptions, and Islam is often framed within the context of security and conflict in contemporary European narratives. This study aims to explore two key aspects: (1) the sentiments associated with collocations related to Islam in European Parliament sessions, and (2) the semantic categorization of these collocations within the corpus. Using collocation and concordance analysis via Corpus Query Processing (CQP), the study finds that themes with absolute negative sentiments are predominantly associated with the term Terrorismus 'terrorism,' which is frequently linked to Islam. However, some other collocations reveal variations in sentiment, including the presence of limited but notable positive sentiments. The study also categorizes these collocations into semantic groups based on established corpus linguistics frameworks, identifying patterns of representation that indicate bias in political discourse toward Islam. These findings highlight the securitization of Islam in political narratives, which may reinforce negative stereotypes and contribute to social polarization. Nevertheless, the existence of references with positive sentiments suggests opportunities to promote more balanced and constructive discourse. This study underscores the importance of inclusive political language to foster social cohesion. Future research is recommended to expand the corpus to other languages, conduct longitudinal analyses, and further explore positive narratives related to Islam to achieve a more balanced political discourse in Europe